6-Formyl-5-isopropyl-3-hydroxymethyl- 7-methyl-1H-indene mitigates methamphetamine-induced photoreceptor cell toxicity through inhibiting oxidative stress. (May 2020) - Xu, H; Jiang, C; Zhao, H; Liu, L
As an extremely addictive psychostimulant drug and an illicit dopaminergic neurotoxin, methamphetamine (METH) conducts to enhance satisfaction, feelings of alertness through influencing monoamine neurotransmitter systems. Long-lasting exposure to METH causes psychosis and increases the risk of neurodegeneration. 6-Formyl-5-isopropyl-3-hydroxymethyl-7-methyl-1H-indene (FIHMI) is a novel compound with potent antioxidant properties. This study was to investigate whether FIHMI could mitigate METH-induced photoreceptor cell toxicity. METH-caused cell toxicity was established in 661W cells and protective effects of FIHMI at different concentrations (1–10 µM) was examined. FIHMI significantly attenuated the METH-caused cell damage in 661W cells, evidenced by increasing cell viability and mitochondrial membrane potential, decreasing cytochrome c release and DNA fragmentation, inhibiting activities of caspase 3/9, and changing expression of apoptosis-related protein. Furthermore, FIHMI treatment decreased mRNA expression of Beclin-1 and LC3B protein expression in METH-induced 661W cells suggesting autophagy is reduced. FIHMI decreased the oxidative stress through increasing protein expression of nuclear factor (erythroid-derived 2)-like 2. These data demonstrated FIHMI could inhibit oxidative stress, which may also play an essential role in the regulation of METH-triggered apoptotic response, providing the scientific rational to develop FIHMI as the therapeutic agent to alleviate METH-induced photoreceptor cell toxicity.